SHIFTING THE DEVELOPMENT OF THE KEMBANG KUNING TOURISM VILLAGE IN A SUSTAINABLE DIRECTION - Irma Agryanti (Bajang Institute, 2025)
In its development, tourist village activities have experienced changes in response to the challenges of developing tourism trends. Changes in tourist villages do not only change the physical layout but also the development which implements sustainability aspects. This research uses a qualitative case study method which aims to explain the process shifting (changes) in developing the Kembang Kuning tourist village in a sustainable direction and finding the factors that influence these changes in order to provide recommendations for future improvements. Data collection was carried out by interviewing Pokdarwis and tourists as well as conducting observation and documentation. Data analysis was carried out by referring to the Miles and Huberman analysis model. Based on the research results, it is known that through stages Unfreeze, Movement And Refreshments can be used as a framework that helps the Kembang Kuning tourist village in managing changes in the development of the tourist village towards sustainability. The changes that occur are based on market competition factors and the need to improve community welfare. From the research results, it was found that this change model was able to overcome resistance and increase community participation in the Kembang Kuning tourist village. It was also found that the Kembang Kuning tourist village had made changes to all components in the development of the tourist village. Acceleration Shifting The development of the Kembang Kuning tourist village is greatly influenced by the presence of agents of change, namely Pokdarwis, collaborative management through CBT and support from the local community, all of which refer to the principles of sustainability.